2016
DOI: 10.1111/fwb.12821
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sources and trophic structure in a macrophyte‐dominated polyculture pond assessed by stable‐isotope analysis

Abstract: Summary Freshwater polyculture systems should efficiently utilise natural food resources and pond habitats with the consequent effects of reducing costs and increasing productivity. However, understanding of the primary carbon sources and food web within polyculture ponds, and especially macrophyte‐dominated ponds, remains limited. Stable‐isotope analysis was used to identify the main carbon sources and describe the trophic patterns of freshwater fauna in a polyculture pond around Lake Gucheng, China. An iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(66 reference statements)
2
3
0
Order By: Relevance
“…Comparisons of SIA values from our study and other studies (Table 3) indicate that TMG in Wales generally have higher δ 13 C and δ 15 N values (i.e., more enriched) than those reported in another study in Great Britain (Britton et al, 2010), indicating a higher trophic level (δ 15 N) and a different primary source of carbon (δ 13 C). Our δ 13 C values are relatively high and closer to the ones reported in China -where topmouth gudgeon is a native species (Mao et al, 2012(Mao et al, , 2016Gao et al, 2017) than to values observed in Belgium where the species is invasive (Tran et al, 2015). High δ 13 C values are more typical of benthic food pathways, compared to pelagic food pathways which tend to be more 13 C depleted (Pinnegar and Polunin, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Comparisons of SIA values from our study and other studies (Table 3) indicate that TMG in Wales generally have higher δ 13 C and δ 15 N values (i.e., more enriched) than those reported in another study in Great Britain (Britton et al, 2010), indicating a higher trophic level (δ 15 N) and a different primary source of carbon (δ 13 C). Our δ 13 C values are relatively high and closer to the ones reported in China -where topmouth gudgeon is a native species (Mao et al, 2012(Mao et al, , 2016Gao et al, 2017) than to values observed in Belgium where the species is invasive (Tran et al, 2015). High δ 13 C values are more typical of benthic food pathways, compared to pelagic food pathways which tend to be more 13 C depleted (Pinnegar and Polunin, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Comparisons of SIA values from our study and other studies (Table 3) indicate that TMG in Wales generally have higher δ 13 C and δ 15 N values (i.e more enriched) than those reported in another study in Great Britain (Britton et al 2010), indicating a higher trophic level (δ 15 N) and a different primary source of carbon (δ 13 C). Our δ 13C values are relatively high and closer to the ones reported in China -where topmouth gudgeon is a native species (Gao et al 2017;Mao et al 2012;Mao et al 2016) than to values observed in Belgium where the species is invasive (Tran et al 2015). High δ 13 C values are more typical of benthic food pathways, compared to pelagic food pathways which tend to be more 13 C depleted (Pinnegar, Polunin 1999).…”
supporting
confidence: 78%
“…This contradictory effect of habitat modification on niche overlaps can be at least partially explained by the difference in ecological similarity of the compared pairs. A study of crayfish, shrimp and snails co‐occurring in aquaculture ponds (Mao et al., 2016) found that epiphytes were the most important carbon sources for both shrimp and crayfish (a range of contributions: 52%–65%), while phytoplankton made up the highest contribution to molluscs (33%–47%). Our results suggested that the competitive outcomes of interspecific trophic interactions might depend on both the availability and diversity of prey and the dietary similarity among sympatric species (Lawlor, 1980).…”
Section: Discussionmentioning
confidence: 99%